Pengaruh Pendekatan Reciprocal Teaching Terhadap Hasil Belajar Bahasa Inggris Peserta didik Kelas VIII.3 SMP N 2 Bonjol - Yonia Mestika (Universitas Negeri Padang, 2019)
This research is motivated by the reality in the field in the application of English lessons in class VIII.3 SMP N 2 Bonjol before using the Reciprocal Teaching approach to learning English. This Classroom Action Research consists of two cycles. Research subjects were 24 teachers and class VIII.3 students. Data analysis was performed using qualitative and quantitative data analysis models. Evaluation of the results obtained in the first cycle reached an average of 70.12. In this cycle there were still some students whose scores were below the KKM, while in the second cycle there was an increase reaching an average of 86.75, with the following details: 4 people scored 100, 1 person got 95, 4 people got 90 points, 7 people got a score of 85, 5 people got a score of 80, 1 person got a score of 78, and 2 people got a score of 77. Evaluation of the results obtained in cycle II was 86.75, an increase compared to the average in the first cycle of 70.12.